DAIR: A Framework for Managing Enterprise Wireless Networks Using Desktop Infrastructure - Bahl, Paramvir; Padhye, Jitu; Ravindranath, Lenin; Singh, Manpreet; Wolman, Alec; Zill, Brian (Proceedings of the Fourth Workshop on Hot Topics in Networking (HotNets-IV), 2005)
We present a framework for managing and troubleshooting enterprise wireless networks using desktop infrastructure. The framework is called DAIR, which for Dense Array of Inexpensive Radios. Prior proposals in this area either rely solely upon access points (APs) and mobile clients to monitor the wireless network, or augment them with dedicated sensor nodes. We believe that these approaches can be improved upon. One cannot cover the entire spectrum in a comprehensive manner using only APs and mobile clients. An ordinary, single-radio AP cannot monitor multiple channels effectively, without adversely impacting the associated clients. Due to power constraints, mobile devices can not continuously monitor the wireless networks. Deploying dedicated sensor nodes is an expensive proposition. Our solution is based on two simple observations. First, in most enterprise environments, one finds plenty of desktop machines with good wired connectivity, and spare CPU and disk resources. Second, inexpensive USB-based wireless adapters are commonly available. By attaching these adapters to desktop machines, and dedicating the adapters to the task of monitoring the wireless network, we create a low cost management infrastructure. In this paper, we show how the DAIR framework is wellsuited for solving many wireless management problems including detection of unauthorized access points, handling malfunctioning APs, and performance monitoring. In each case, we show how the DAIR framework takes advantage of the key attributes of the desktop infrastructure: dense deployment, stationarity, wired connectivity, and spare CPU and disk resources.